A 5-GHz radio front-end with automatically Q-tuned notch filter and VCO. - Rogers, J.W.M.
A low-voltage receiver front-end for 5-GHz radio applications is presented. The receiver consists of a low-noise amplifier (LNA) with notch filter, a voltage-controlled oscillator (VCO), and a mixer. The LNA/notch filter has an automatic Q-tuning circuit integrated with it to provide good image rejection. On-chip transformers are used extensively in the receiver to improve performance and facilitate low-voltage operation. The receiver has a gain of 19.8 dB, noise figure of 4.5 dB, a third-order input intercept point (IIP3) of -11.5 dBm, and an image rejection of 59 dB, and the VCO had a phase noise of -116 dBc/Hz at 1-MHz offset.
Keywords: 19.8 dB; 4.5 dB; 5 GHz; Automatic Q-tuning circuit; Image rejection; Low-noise amplifier; Low-voltage front-end.; Mixer; Notch filter; On-chip transformer; Phase noise; Radio receiver; Third-order input intercept point; Voltage-controlled oscillator; Wireless communication